Tetris in the Nervous System: What Principles of Neuronal Tiling Can Tell Us About How Glia Play the Game - DeSantis, Dana F.; Smith, Cody J. (Frontiers in Cellular Neuroscience, 2021)
Precise organization and arrangement of neural cells is essential for nervous system functionality. Cellular tiling is an evolutionarily conserved phenomenon that organizes neural cells, ensuring non-redundant coverage of receptive fields in the nervous system. First recorded in the drawings of Ramon y Cajal more than a century ago, we now have extensive knowledge of the biochemical and molecular mechanisms that mediate tiling of neurons. The advent of live imaging techniques in both invertebrate and vertebrate model organisms has enhanced our understanding of these processes. Despite advancements in our understanding of neuronal tiling, we know relatively little about how glia, an essential non-neuronal component of the nervous system, tile and contribute to the overall spatial arrangement of the nervous system. Here we discuss lessons learned from neurons and apply them to potential mechanisms that glial cells may use to tile, including cell diversity, contact-dependent repulsion, and chemical signaling. We also discuss open questions in the field of tiling and what new technologies need to be developed in order to better understand glial tiling.